Jatobá (Hymenaea sp.) as a wheat substitute in plant-based cookies to improve its nutritional quality (Research, Society and Development, 2022)
Jatoba (Hymenaea sp.) is a Brazilian savanna fruit with low lipid content, high amounts of dietary fiber, protein and minerals like calcium, iron, and zinc.  Despite the lack of studies, due to jatoba nutritional characteristics, it could be used to replace wheat on plant-based cookies, improving their nutritional quality. Therefore, this study aimed to evaluate the use of jatoba flour to replace wheat flour in plant-based cookies regarding chemical composition and physical characteristics. Cookies were prepared with 25%, 50%, 75% and 100% of jatoba flour replacing wheat flour and, subsequently, physical parameters (cooking factor, diameter, thickness and spread rate) and chemical composition were evaluated. Regarding the cooking factor, there was no significant difference between the samples, the cookies’ diameters were smaller in the samples 25%, 50% and 75% compared to the control sample and 100%.I In the thickness parameter the control sample showed a smaller value compared to the preparations made with jatoba and the spreading rate showed a significant difference from the control sample to the others, however the samples 25%, 50%, 75% and 100% did not differ from each other. Plant-based cookies with jatoba flour were higher in fiber, calcium, magnesium, iron, zinc content than the control sample (100% based on wheat flour). Jatobá flour is a good alternative to improve the nutritional quality of plant-based cookies.